Proteomics of osteosarcoma. (June 2014) - Bernardini, Giulia; Laschi, Marcella; Geminiani, Michela; Santucci, Annalisa
<x xml:space="preserve">Abstract</x> Osteosarcoma (OS) is the most common primary malignant tumor of bone and the third most common cancer in childhood and adolescence. Nowadays, early diagnosis, drug resistance and recurrence of the disease represent the major challenges in OS treatment. Post-genomics, and in particular proteomic technologies, offer an invaluable opportunity to address the level of biological complexity expressed by OS. Although the main goal of OS oncoproteomics is focused on diagnostic and prognostic biomarker discovery, in this review we describe and discuss global protein profiling approaches to other aspects of OS biology and pathophysiology, or to investigate the mechanism of action of chemotherapeutics. In addition, we present proteomic analyses carried out on OS cell lines as in vitro models for studying osteoblastic cell biology and the attractive opportunity offered by proteomics of OS cancer stem cells.